Green finance and total factor energy efficiency: theoretical mechanisms and empirical tests - Yu, Shihai; Wang, Simin; Cheng, Xiaolan; Li, Lei (Frontiers in Environmental Science, 2024)
China's green financial pilot policies (GFPP) is an important start to build a green financial system in China. It is also an important part of achieving the "dual-carbon" goal. This paper calculates China's total factor energy efficiency (TFEE), analyzes the impact of GFPP on TFEE, and explores the conduction mechanism. The results show that the relationship between GFPP and TFEE in the pilot areas is statistically significant. GFPP mainly improves TFEE through the green innovation effect and the optimization of energy structure. GFPP has a significant effect on TFEE enhancement in eastern coastal cities, non-old traditional industrial cities, and non-resource-based cities with high initial energy. China should continue to deepen the pilot work of green finance, formulate differentiated green finance policies, and ensure green technology innovation. This study provides empirical evidence for further optimization of green finance and energy efficiency.